Excluded volume effect of surfactant ligands on the shape of nascent nanocrystal - Andrij Baumketner; Dmytro Anokhin; Yaropolk Patsahan (Condensed Matter Physics, 2025)
We investigate the effect of the excluded volume of surfactant ligands on the shape of incipient quantum dots (QDs) to which they are attached. We consider a model in which ligands are represented by hard-sphere particles that are bound to the surface of a nanoparticle (NC) that is cast in the shape of a prism. It is found in Monte Carlo simulations that the ensemble of relevant NC conformations consists of a small number of specific states that take on the form of nanoplates and nanorods. The shape of these states can be well described by the derived theoretical models. At increasing ligand density, the free energy of different states is seen to be approximately the same, suggesting that excluded volume interactions among ligands acts to narrow down the conformational  space accessible to an NC without creating a statistical preference for any particular configuration.